2022
DOI: 10.1002/epi4.12616
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 pandemic on epilepsy care in Japan: A national‐level multicenter retrospective cohort study

Abstract: Objective The impact of the coronavirus disease 2019 (COVID‐19) pandemic on epilepsy care across Japan was investigated by conducting a multicenter retrospective cohort study. Methods This study included monthly data on the frequency of (1) visits by outpatients with epilepsy, (2) outpatient electroencephalography (EEG) studies, (3) telemedicine for epilepsy, (4) admissions for epilepsy, (5) EEG monitoring, and (6) epilepsy surgery in epilepsy centers and clinics across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…In a cross-sectional study of 255 consecutive patients assessed by telephone, Fonseca and colleagues (2020) found a signi cant difference in the prevalence of COVID-19 between people with worsening non-worsening epilepsy (75.6% and 23.7%, respectively, with p < 0.0001) [29]. Also, the rate of vaccination was signi cantly lower in people with worsening epilepsy than non-worsening epilepsy (39.5% versus 68.4% respectively) with P = 0.003, and this nding agrees with previous research that was conducted in Italy by Romozzi and colleaguesin 2022 [34], who studied the safety and tolerability of COVID- This study demonstrated that the COVID-19 pandemic resulted in delayed neurology appointments and more di culty going to the pharmacy and getting medication in worsening than non-worsening epilepsy, which is consistent with Albert and colleagues and Kuroda and colleagues [35,36] as well as reduced access to ASM [24]. The current study also found that work di culties were more pronounced among people with worsening epilepsy, consistent with a general effect of increased seizure rate on patients' daily activities.…”
Section: Discussionsupporting
confidence: 91%
“…In a cross-sectional study of 255 consecutive patients assessed by telephone, Fonseca and colleagues (2020) found a signi cant difference in the prevalence of COVID-19 between people with worsening non-worsening epilepsy (75.6% and 23.7%, respectively, with p < 0.0001) [29]. Also, the rate of vaccination was signi cantly lower in people with worsening epilepsy than non-worsening epilepsy (39.5% versus 68.4% respectively) with P = 0.003, and this nding agrees with previous research that was conducted in Italy by Romozzi and colleaguesin 2022 [34], who studied the safety and tolerability of COVID- This study demonstrated that the COVID-19 pandemic resulted in delayed neurology appointments and more di culty going to the pharmacy and getting medication in worsening than non-worsening epilepsy, which is consistent with Albert and colleagues and Kuroda and colleagues [35,36] as well as reduced access to ASM [24]. The current study also found that work di culties were more pronounced among people with worsening epilepsy, consistent with a general effect of increased seizure rate on patients' daily activities.…”
Section: Discussionsupporting
confidence: 91%
“…These seizures were associated with higher patient age and a higher prevalence of altered consciousness compared to the pre-pandemic period. During the pandemic period, some societies recommended reducing in-person healthcare facility visits for PWE with stable seizures, which decreased outpatient visits and admissions in epilepsy centers [31] . Our results might indicate that PWE with non-life-threatening status but a need for medication avoided calls to EMS, as in another study on stroke patients [32] .…”
Section: Discussionmentioning
confidence: 99%